Self-criticism and psychotherapy outcome: A systematic review and meta-analysis - Löw, Christina Alexandra; Schauenburg, Henning; Dinger, Ulrike (Clinical psychology review, 2020)
Self-criticism involves constant and harsh self-scrutiny, overly critical evaluations of one’s own behavior, and negative reactions to perceived failures in terms of active self-bashing. Self-criticism is associated with various mental disorders and psychotherapy outcome. This paper provides (1) a meta-analysis of the association between pre-treatment self-criticism and multiple treatment outcomes, and (2) a systematic review of the association between change in self-criticism and therapy outcome. Based on a systematic literature search, 49 longitudinal studies (56 independent effect sizes; 3277 patients) were included in the meta-analysis and 7 studies were identified for the additional systematic review. A random-effects meta-analysis was performed to assess the magnitude of the association between self-criticism and outcome, also considering potential moderators. The overall association between pre-treatment self-criticism and psychotherapy outcome was r = -.20 (95% CI = -.25 - -.16, p < .0001), suggesting that higher levels of self-criticism are related to poorer outcome. Although effect sizes showed little heterogeneity, the association varied by type of mental health problem and indicated stronger associations with certain disorders (e.g., eating disorders). The review based on change scores yielded inconsistent results. Our findings support the relevance of self-criticism for psychotherapy outcome.